Anatomical and clinical perspectives on the distal humeral fossae: A study in South Indian dry bones - Nandini Prashanth Bhat; Ashwija Shetty; Kurian Alapatt; Nom Kumar Naik Bhukya; Sushma Prabhath; Suhani Sumalatha (Translational Research in Anatomy)
Background: The distal end of the humerus features three fossae—radial, coronoid, and olecranon—that accommodate the processes of the forearm bones during elbow movements. Variations in their morphology and morphometry can influence joint biomechanics, fracture fixation, and prosthesis design. However, comprehensive data on all three fossae in South Indian dry humeri remain limited. This study aims to fill this gap by providing clinically relevant morphometric insights. Methodology: A total of 120 adult dry humeri (60 right, 60 left) of unknown age and sex were analyzed. Standardized photographs were evaluated using ImageJ software. Sixteen parameters—including the length, width, and circumference of each fossa—were measured. Data were analyzed using descriptive statistics, Pearson's correlation, and t-tests. Results: The left humerus was significantly longer (mean difference 1.96 cm) and had a greater distal width (mean difference 0.58 cm) than the right. The coronoid fossa was longer (mean difference 0.13 cm) and had a greater circumference on the right (mean difference 0.23 cm), while the radial and olecranon fossae were larger on left. Morphological analysis identified five olecranon fossa types, with oval being most common (44 %). The coronoid and radial fossae were predominantly triangular. No significant correlation was observed between humeral length or width and fossa circumference. The supratrochlear foramen, an anatomical variation which was found in 28.3 % of bones. Conclusion: These findings have important implications for orthopedic surgery, such as intramedullary fixations, prosthetic design for elbow reconstruction, and forensic anthropology.